Remote Iron dynamics of NiFe (oxy)hydroxides toward robust active sites in water oxidation - Jianxiong Zhao; Yuwei Zhang; Yike Ye; Qiucheng Xu; Songzhu Luo; Fanxu Meng; Siyuan Zhu; Xiaoning Li; Xinlong Lin; Anke Yu; Xiao Ren; Tianze Wu; et al. (Nature Communications)
Abstract Ni(Fe) (oxy)hydroxides have long been recognized as benchmark electrocatalysts for water oxidation in alkaline media. Maximizing their activity and longevity will be vital for facilitating scalable water electrolysis. However, progress is hindered by insufficient understandings of surface Fe dynamics and by the absence of effective regulatory approach. Here we show the surface Fe dynamics beyond the immediate vicinity of Ni(Fe) oxyhydroxides on working electrode but being remotely influenced by Fe diffusion and deposition on the counter electrode. While Fe could be highly active in reversible dynamics, disruptions in this process can result in significant activity decay due to the loss or deactivation of surface Fe species. On-site regulation of Fe dynamics is inspired by pre-catalysts. [Ni0.75Fe0.25]0.6Zn0.4Clx derives Ni(Fe) oxyhydroxide with enhanced performance due to Zn leaching and cation defects that improve Fe site accommodation. Theoretical studies suggest that Fe dissolution occurs when cation defects are lacking but shifts to Fe capture as defects increase, underscoring on-site defect manipulation to maintain the abundance of active Fe sites.